1972
DOI: 10.1016/0014-5793(72)80646-x
|View full text |Cite
|
Sign up to set email alerts
|

Structure primaire de la paracaseine κ bovine

Abstract: The complete amino acid sequence of bovine para-rcasein is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 15 publications
0
7
0
3
Order By: Relevance
“…In the bovine caseins it has been shown that the phosphorylated serine residues are all followed by an acidic amino acid two residues downstream [21] and that the phosphorylated residues are clustered in a region rich in acidic amino acids [3]. The same could hold true for mouse F casein.…”
Section: Gac Atc Att Tct Cag Caamentioning
confidence: 93%
See 1 more Smart Citation
“…In the bovine caseins it has been shown that the phosphorylated serine residues are all followed by an acidic amino acid two residues downstream [21] and that the phosphorylated residues are clustered in a region rich in acidic amino acids [3]. The same could hold true for mouse F casein.…”
Section: Gac Atc Att Tct Cag Caamentioning
confidence: 93%
“…3) the aminoterminal methionine is followed in all but one case (ovine CI lactalbumin) by either a lysine or an arginine, which also might be important in stabilizing the nascent-chain -membrane-receptor complex through additional ionic bonds [20]. The amino acid sequences of all bovine caseins have been determined [2,3]. Mature mouse E casein and mature bovine c(,2 casein show partial homology in their N-terminal region (Fig.4A).…”
Section: Gac Atc Att Tct Cag Caamentioning
confidence: 99%
“…Known phosphoserine residues in the bovine sequence [24] are indicated (by P). Potential phosphoserine residues in the bovine and guinea-pig sequences are indicated by asterisks.…”
Section: Comparison Of Bovine Usz Casein With the Deduced Guinea-pig mentioning
confidence: 99%
“…The K-casein molecules consist of two parts separated by the chymosin-sensitive bond (Jolles, 1966;Delfour et al, 1965; see also below): para-K-casein (NH2-terminal moiety, residues 1-105) and K-caseinoglycopeptide (COOH-terminal moiety, residues 106-169 for cow and 106-171 for sheep K-caseins). The primary structures were previously described by Brignon et al (1972) and Jolles et al (1972) for cow para-Kcasein, Mercier et al (1972) andJolles et al (1973) for cow K-caseinoglycopeptide and by Jolles et al (1974) for sheep K-casein (Fig.. 1). We wish to discuss the secondary structures of both K-caseins and of some of their biologically important sites (see below).…”
Section: Resultsmentioning
confidence: 97%